From collection: Eight years war between Iran and Iraq. These posters come from the art gallery Sooresh. They show the work of the most important Iranian revolutionary artists
From collection: Eight years war between Iran and Iraq. These posters come from the art gallery Sooresh. They show the work of the most important Iranian revolutionary artists.